2022
DOI: 10.3390/ijms23126592
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of NANOS1 and NANOS3 in the Cell Cycle and NANOS3-PUM1-FOXM1 Axis to Control G2/M Phase in a Human Primordial Germ Cell Model

Abstract: Nanos RNA-binding proteins are critical factors of germline development throughout the animal kingdom and their dysfunction causes infertility. During evolution, mammalian Nanos paralogues adopted divergent roles in germ cell biology. However, the molecular basis behind this divergence, such as their target mRNAs, remains poorly understood. Our RNA-sequencing analysis in a human primordial germ cell model‑TCam-2 cell line revealed distinct pools of genes involved in the cell cycle process downregulated upon NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Moreover, it is a well-known oncogene. FOXM1 was shown to bind to the promoter of NANOS3 in a human germ cell model [ 54 ]. This study showed a mechanism in which NANOS3 expression is induced by FOXM1; in return, NANOS3 represses FOXM1 through 3’UTR of its mRNA.…”
Section: Dysregulation Of Nanos Transcriptional Regulators In Cancermentioning
confidence: 99%
“…Moreover, it is a well-known oncogene. FOXM1 was shown to bind to the promoter of NANOS3 in a human germ cell model [ 54 ]. This study showed a mechanism in which NANOS3 expression is induced by FOXM1; in return, NANOS3 represses FOXM1 through 3’UTR of its mRNA.…”
Section: Dysregulation Of Nanos Transcriptional Regulators In Cancermentioning
confidence: 99%
“…To assess the reliability of the RNA-seqs data, we further determined the expression profiles of germline marker genes tdrd7 , nanos1 , klf5 , igtb1 , hsd17b4 and rad51 in a panel of tissues or cells, including testis, ovary, the cultured ovarian cells, liver, spleen and kidney, since these genes have been documented in many species [ 37 , 38 , 39 , 40 , 41 , 42 ]. As described above, the morphology of cells became more uniform from passage 20 ( Figure 1 C), therefore, the expression profile of these marker genes was examined using cells at passage 20.…”
Section: Resultsmentioning
confidence: 99%
“…NANOS proteins are also implicated in cancer, in connection with their capacity to control cell proliferation, differentiation and apoptosis. Moreover, alterations of NANOS 1, NANOS 2 or NANOS 3 expression levels correlate with tumorigenesis in a complex pattern [1,4,[9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%